Vocational education and training in the Netherlands : short description - Maes, Martine [Verfasser] (Office for Official Publications of the European Communities, 2004)
"One of the distinguishing marks of Dutch vocational education and training is that there is a deliberate policy to develop VET as a separate and distinct pathway to high level qualifications. Another feature is a very high level of regionalisation and decentralisation, which results in education and training institutions being given a great deal of freedom and responsibility in resource management, both human and financial. A comprehensive competence-based qualification structure is also being introduced." (Author's abstract)
Keywords: Berufsbildungssystem; Berufsausbildung; Berufliche Weiterbildung; Kompetenzentwicklung; Bildungspersonal; Berufsberatung; Bildungsfinanzierung; Niederlande